From MERS to COVID-19 and Omicron: Recent Evolution of RNA Coronaviruses - Einstein, George P.; Tulp, Orien L. (Research Highlights in Disease and Health Research Vol. 7, 2023)
The purpose of the study is to briefly review the evolution and development of the MERS, SARS. and COVID-19 coronaviruses. One alarming finding about COVID-19 is that people with SARS-CoV-2 infection can spread the virus to others while asymptomatic and frequently before they have manifested overt symptoms of disease. Additionally, once infected, the virus may attack multiple organs and tissues, including the brain, cardiovascular system, lungs, and other organs in its new host. The recent emergence and identification of the Delta, Omicron and other variants continue to spread globally, often despite prior vaccination and boosters with any of the currently approved vaccines or with natural immunity from previous infection.